Analisis Kelimpahan Dan Keanekaragaman Perifiton Rawa Bangkau Kabupaten Hulu Sungai Selatan Kalimantan Selatan - Deddy Dharmaji; Suhaili Asmawi; Yunandar Yunandar; Rio Rizky Kurniawan (Universitas Lambung Mangkurat, 2020)
Periphyton group are biota communities that be able adapt and grow well in lentic waters. Their habits are adhere to a permanent location. Aquatic vegetation in Bangkau can influenced the periphyton abundance and diversity as natural food in the food chain. The purpose of this study was to analyzed abundance and diversity of Periphyton from different aquatic vegetation. The research was conducted in three stations by purposive sampling. The method used was quantitative explored. The data that has been taken were epiphythic periphyton samples. Periphyton sampling procedures, preservation, and analysis were carried out based on Indonesian National Standard methods. Bangkau’s peatland had the highest abundance of phytoplankton-periphyton (9982 sel/liter) in inlet, but low at middle station (778 sel/liter). Zooplankton-periphyton (553 sel/liter) in middle station was the highest abundance whereas in outlet station (153 sel/liter) was the lowest. Bacillariophyceae had predominant and always attendanced Oscillatoria, Closterium, Planktonella, Diatom, meanwhile zooplankton-periphyton dominated Ciliophora in all stations and sampling. Diversity index of phytoplankton-periphyton in inlet station (1,55) was the highest and in inlet (0,77) was the lowest. Zooplankton-periphyton in middle (1,76) and outlet (0,94) was different based on Shannon wiener’s Index. The abundance index of Bangkau were mesotrophic categorized for phytoplankton-periphyton and oligotrophic for zooplankton-periphyton. Due to the low level of species diversity (H’≤ 3) showed moderate stability and for the water quality conditions was moderate polluted.